Behavior Changes in Paulo Coelho Veronika Decides to Die: A Psychological Approach - Bagas Suryo Prakoso; Resneri Daulay (NOTION: Journal of Linguistics, Literature, and Culture, 2020)
The purpose of this study is to analyze the personality of the main character presented in the novel. In addition, the aim of this research is to reveal the main character’s environments contribute to the character’s motivation to life. This novel conducted the struggle from Veronika as the main character for finding her motivation to life. This study used descriptive qualitative methods to analyze the data. This study used three main concepts of social cognitive theory by Albert Bandura (1986), they are reciprocal determinism, therapy, and dysfunction behavior/depression. This study also applied the theory of social cognitive theory in the book entitled The Theory of Personality by Jess Feist as a tool to analyze the personality of the main character also the main character’s environments contributing to the character’s motivation to life in the novel. The results are first, this study indicated personality of Veronika as the main character in the novel based on the social cognitive theory concept that is dysfunction behavior. It shows that Veronika is an introvert person, fainthearted, and suffering from depression. Second, this study discovered the main character’s environments contribute to the character’s motivation to life based on the social cognitive concepts, they are reciprocal determinism and therapy. Based on that theoretical concept, it shows that Veronika’s environment really helps her to find her motivation to life. They are Mari, Zedka, and Edward.